A randomised controlled trial to explore attitudes to routine scale and polish and compare manual versus ultrasonic scaling in the general dental service in Scotland [ISRCTN99609795] - Smith Patricia A; Young Linda; Bonner Brian C; McCombes Wendy; Clarkson Jan E (BMC, 2005)
Abstract Background To investigate, within general dental practice, patients' and vocational dental practitioners' (VDP) attitudes towards the benefits and costs of a simple scale and polish and to compare the experience of using manual versus ultrasonic instruments to scale teeth. Methods 28 VDPs and 420 patients participated. Patients were randomly allocated to either group. Patients' and VDPs' attitudes towards, and experience of, the scale and polish were elicited by means of self-administered questionnaires. Results The majority of patients (99%) believed a scale and polish was beneficial. VDPs considered ultrasonic treatment to be appropriate on significantly more occasions than they did for manual scale and polish (P < 0.001). Patient discomfort: with ultrasonic scaling 69.2% felt 'a little uncomfortable' or worse compared with 60% of those undergoing manual treatment (P = 0.072). VDPs considered treatment charges were appropriate for 77% of patients. Conclusion Routine scaling and polishing is considered beneficial by both patients and vocational trainees. The majority of patients, regardless of treatment method, experience some degree of discomfort when undergoing a scale and polish. VDPs showed a preference for the ultrasonic treatment method.